2012
DOI: 10.1016/j.gloenvcha.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Social-ecological and regional adaptation of agrobiodiversity management across a global set of research regions

Abstract: A B S T R A C TTo examine management options for biodiversity in agricultural landscapes, eight research regions were classified into social-ecological domains, using a dataset of indicators of livelihood resources, i.e., capital assets. Potential interventions for biodiversity-based agriculture were then compared among landscapes and domains. The approach combined literature review with expert judgment by researchers working in each landscape. Each landscape was described for land use, rural livelihoods and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 80 publications
3
76
0
Order By: Relevance
“…Although the literature is rich in methods for assessing disturbance and related land use intensity , unambiguous, quantitative units remain elusive (Jackson et al 2012). The present study showed that subjectively determined land use intensity and disturbance gradients correspond closely with changes in plant species and PFT diversities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature is rich in methods for assessing disturbance and related land use intensity , unambiguous, quantitative units remain elusive (Jackson et al 2012). The present study showed that subjectively determined land use intensity and disturbance gradients correspond closely with changes in plant species and PFT diversities.…”
Section: Discussionmentioning
confidence: 99%
“…Projected adaptive actions include improving plant performance (for example, nutrition, yields, food quality) in response to elevated CO 2 and rising temperatures [26][27][28]; avoiding pest damage and food waste [28,29]; developing forecasting, management and insurance options to decrease the risk due to unexpected rainfall patterns, higher temperatures and shifting length in growth seasons [14,28,30]; and managing natural resources at the landscape and regional levels to assure the environmental quality and ecosystem services upon which agriculture depends [31][32][33]. Solutions involve trade-offs.…”
Section: Introductionmentioning
confidence: 99%
“…The wide-ranging interactions of agrobiodiversity amid global change encompass: (a) the management, quality, and access to livelihood-related resource inputs (e.g., skills, knowledge, and labor engaged directly with agrobiodiversity and supporting resources, such as soils and water) amid the livelihood diversification of food-growers [12][13][14]; (b) ecosystem services and specifically interactions within agrobiodiversity-supporting ecological systems (plant-soil interactions) [10,15]; (c) crop and food-growing strategies using agrobiodiversity for combined economic, environmental, and cultural rationales [16][17][18][19][20][21] including agrodiversity, which refers to management of environmental variation in agriculture [5,22]; (d) adaptation, resilience, and mitigation in response to climate change [23][24][25][26][27]; (e) biodiversity use and conservation [9,[28][29][30][31][32]; (f) market opportunities [33,34]; and (g) food security and sovereignty together with nutrition and dietary diversity and human well-being [35][36][37][38][39]. Each of the above linkages is receiving increased research and policy interest that includes synthesis treatments of multiple linkage types [40,41].…”
mentioning
confidence: 99%